CORPORATE SOCIAL RESPONSIBILITY: UPAYA MEMAHAMI ALASAN DIBALIK PENGUNGKAPAN CSR BIDANG PENDIDIKAN - Naraduhita, Dea Cendani; Sawarjuwono, Tjiptohadi (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2012)
Corporate Social Responsibility (CSR) is a corporate commitment to include social and environmentalaspects into every operation. Thus, corporate responsibility is not longer confined tothe company's financial responsibility towards the shareholdernya, but more broadly tostakeholders as a whole. The main concept of CSR is sustainable development, which means anactivity carried out more than just philantropy or charity events. Since made regulationsregarding the activities relating to Corporate Social Responsibility (CSR), ie in Act No. 40 year2007 regarding Limited Liability Companies, CSR has now become a liability law for thecompany in Indonesia. Therefore, now many companies those carry out those activities.Nevertheless, in accounting there has been no clear rule regarding the reporting of CSRactivities. IAI itself, in SFAS No. 1, implicitly conveys that the company can also provideadditional reports on matters which is added value in their financial statements. This study aimsto analyze and compare the various CSR activities undertaken in education by several leadingcompanies in Indonesia. The method used is the method of Library Studies (Library Research).Therefore, the object of research include the Annual Report and Sustainability Report (if any),and other articles related to that can be obtained online or through other sources. Ten companieshave been used as a sample research report or include elements of CSR into the company'sAnnual Report, although the actual reporting on matters such as CSR is still highly voluntary. Theresults obtained showed that each company has a flagship program different associated with theirCSR activities to the field of education.Keywords:corporate social responsibility, education, annual report, sustainability report